Kewenangan Pemerintah Kabupaten/Kota dalam Pelayanan Terpadu Satu Pintu untuk Mewujudkan Masyarakat yang Sejahtera (SETARA : Jurnal Ilmu Hukum, 2023)
This article examines the authority of district and municipal governments in one-stop integrated services as an instrument for achieving public welfare. The issue is important because decentralization and regional autonomy require local governments not only to regulate, but also to provide efficient, accessible, and investment-supportive public services. Using empirical juridical research, the article reviews the legal basis of one-stop integrated services, the institutional role of regional investment and licensing offices, and practical indicators of service quality. The study finds that district and municipal authority in one-stop services includes licensing and non-licensing matters delegated by regional governments, investment administration, issuance and revocation of permits, and collection of lawful retributions. The article also finds that an ideal one-stop service model depends on integrated administration, information technology, clear procedures, complaint handling, and institutional concentration of authority within a single service body. It concludes that strengthening local authority through an efficient one-stop system can improve public service quality, encourage investment, and support broader social welfare.
Keywords: Government Authority; One-Stop Integrated Services; Public Service; Regional Government; Public Welfare